2017
DOI: 10.36685/phi.v3i1.108
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors in Road Traffic Accident in the City of Palu, Indonesia

Abstract: Background: Traffic accidents are unpredictable events when they occurred. Thus, understanding the risk factors in road traffic injuries is needed.Objective: This study aims to analyze the risk factors in road traffic accidents in the city of Palu.Methods: This was an observational analytic study using case-control approach with sample of 182 respondents consisting of 91 cases and 91 controls. Purposive sampling was used based on a certain considerations made by the researchers themselves. Data were tested wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…16 Based on multivariate analysis in this study, indicating that less alert was proven to be a risk factor for motorcycle traffic accidents with values (p=0.005, OR=4.255, 95% CI=1.540-11.759) means less alert when driving a chance for motorcycle traffic accidents by 4.2 times compared to bikers who are wary. The result of this research is in line with the research of Arifuddin et al 21 found that careless The best protection is the distance between riders and other road users. If a person makes a mistake, a safe distance allows time to react and see opportunities to avoid.…”
Section: Discussionsupporting
confidence: 89%
“…16 Based on multivariate analysis in this study, indicating that less alert was proven to be a risk factor for motorcycle traffic accidents with values (p=0.005, OR=4.255, 95% CI=1.540-11.759) means less alert when driving a chance for motorcycle traffic accidents by 4.2 times compared to bikers who are wary. The result of this research is in line with the research of Arifuddin et al 21 found that careless The best protection is the distance between riders and other road users. If a person makes a mistake, a safe distance allows time to react and see opportunities to avoid.…”
Section: Discussionsupporting
confidence: 89%
“…This causes high side frictions due to the large number of pedestrians, vehicles parked on the side of the road, vehicles coming in and out, and slowing vehicles. This condition is certainly very influential on the safety of road users which allows accidents due to these side frictions [9]. The description of the side friction force on the three roads is presented in the following figure.…”
Section: Side Frictionmentioning
confidence: 99%
“…The traffic accident that occurred in Palu City involved motor vehicles, pedestrians, and bicycle users [8]. The causes of traffic accidents in Palu City include; undisciplined behavior, exceeding the speed limit and not having a driver's license [9]. In addition, road and environmental factors have contributed to the occurrence of traffic accidents, for example damaged road pavements and non-standard road facilities such as inappropriate road median openings [10].…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Undang-undang Nomor 22 Tahun 2009 tentang Lalu Lintas dan Angkutan Jalan pasal 1 poin 24 menjelaskan definisi kecelakaan lalu lintas sebagai suatu peristiwa di jalan yang tidak diduga dan tidak disengaja melibatkan kendaraan dengan atau tanpa pengguna jalan lain yang mengakibatkan korban manusia dan/atau kerugian harta benda. Kecelakaan lalu lintas umumnya terjadi karena berbagai faktor penyebab seperti faktor manusia yang diakibatkan karena pelanggaran atau tindakan tidak hati-hati para pengguna (pengemudi dan pejalan kaki), faktor jalan, faktor lingkungan dan faktor kendaraan (Arifuddin et al 2017;Putra 2019;Sugiyanto 2017). Salah satunya kurangnya investasi pada suatu sistem jaringan transportasi dalam kurun waktu yang cukup lama dapat mengakibatkan sistem prasarana transportasi tersebut menjadi sangat rentan terhadap kemacetan dan kecelakaan yang terjadi apabila volume arus lalu lintas meningkat lebih dari rata-rata.…”
Section: Pendahuluanunclassified